Nietzschean narratives - Shapiro, Gary, 1941- (Studies in phenomenology and existential philosophy., 1989)
Taking issue with a widely held view that Nietzsche's writings are essentially fragmentary or aphoristic, Gary Shapiro focuses on the narrative mode that Nietzsche adopted in many of his works. Shapiro proposes a reading of Nietzsche that recognizes his rigorous critique of the metanarratives of traditional philosophy and religion but that also takes seriously the philosopher's claim to be a master of many styles. By articulating the stories and the critique of story-telling to be found in Nietzsche's writings, Nietzschean Narratives explores the radically plural and yet inevitable nature of the narrative function. Shapiro offers extended readings of three emblematic but contrasting narrative works--Thus Spoke Zarathustra, The Antichrist, and Ecce Homo. His approach is informed by the tension between the critical and the poetic sides of Nietzsche's narrative thought and practice and by the issues raised in recent literary and philosophical discussions of Nietzsche's writing. Such Nietzschean themes as eternal recurrence, the question of origins, and the problematics of self-knowledge are reinterpreted in the context of the narratives in which Nietzsche develops or employs them.